Global Prediction of Recessions - Jonas Dovern; Florian Huber (University of Heidelberg, Department of Economics, 2015)
We present evidence that global vectorautoregressive (GVAR) models produce significantly more accurate recession forecasts than country-specific time-series models in a Bayesian framework. This result holds for most countries and forecast horizons as well as for several country groups.
urn:nbn:de:bsz:16-heidok-183811
Keywords: 330; GVAR; recession forecast; QPS; probability forecast